(untitled) (Research, Society and Development, 2021)
Parafunctional habits are characterized by the repetition of acts that are not related to the normal functions of the stomatognathic system. This research aims to verify the parafunctional habits practiced, perceived and reported by patients and to verify the relationship with the fractures of direct composite resin restorations. Information from 205 patients, seen at the University Dental Clinic of the State University of Londrina, was collected. After data collection, a survey and synthesis of reported parafunctional habits was performed and correlated with the fracture of composite resin restorations. The information and data were tabulated and analyzed using descriptive statistics, COUNTIF function, and the results were expressed in tables. The most frequent parafunctional habits were bruxism, followed by onychophagia, occurring in greater quantity in females. A greater number of fractured restorations were found in patients with parafunctional habits. Among the parafunctional habits verified, it was concluded that bruxism was the most frequent, related mainly to the fracture of class V restorations.